Effect of High‐Power LED Barriers on Shear Bond Strength and Curing Time in Orthodontic Brackets With Single‐Component Adhesive - Yasaman Bozorgnia; Mahla Tak; Maryam Jamali (Clinical and Experimental Dental Research)
ABSTRACT Objective The dental light‐curing unit is a crucial component in bonding brackets. Since it cannot be steam‐sterilized, it is covered with a disposable barrier and disinfected between patients. This study examined the impact of the cellophane layer used to cover the light guides on both the shear bond strength and the adhesive remnant index. Material and Methods Fifty human premolars, extracted for clinical purposes, were randomly allocated into five groups. Three of these groups were cured using a high‐power LED unit with a cellophane layer, applying curing times of 3, 6, and 9 s. The remaining two groups were cured for 3 and 6 s without a cellophane layer. The bracket shear bond strengths were assessed utilizing a universal testing machine. The collected data underwent analysis through a one‐way analysis of variance (ANOVA), followed by Tukey's post hoc test. Results The group with the highest shear bond strength was group 5 (6 s of light curing without a cellophane layer), while group 1 (3 s of light curing with a cellophane layer) had the lowest shear bond strength. Significant statistical differences were identified among the groups (p < 0.05). Moreover, no notable differences were observed concerning the adhesive remnant index. Conclusion The cellophane layer decreased the shear bond strength. Therefore, to achieve clinically accepted values, at least 9 s of radiation is necessary when using cellophane.